2021
DOI: 10.1002/ctm2.627
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of potent And‐1 inhibitors for cancer treatment

Abstract: A cidic n ucleoplasmic D NA‐binding protein 1 (And‐1), an important factor for deoxyribonucleic acid (DNA) replication and repair, is overexpressed in many types of cancer but not in normal tissues. Although multiple independent studies have elucidated And‐1 as a promising target gene for cancer therapy, an And‐1 inhibitor has yet to be identified. Using an And‐1 luciferase reporter assay to screen the Library of Pharmacologically Active Compounds (LOPAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…In the experiment, the estrogen receptor modulator bazedoxifene (BZA) showed a outstanding performance, it can significantly inhibit the expression of WDHD1 in a variety of cell lines at the administered dose. Our study demonstrated that WDHD1 degraders enhanced the sensitivity of platinum‐resistant ovarian cancer and non‐small‐cell lung cancer to platinum‐based drugs and radiotherapy in vitro and in vivo (Gou et al, 2022; Li et al, 2021). BZA degraded WDHD1 by inducing its ubiquitination.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the experiment, the estrogen receptor modulator bazedoxifene (BZA) showed a outstanding performance, it can significantly inhibit the expression of WDHD1 in a variety of cell lines at the administered dose. Our study demonstrated that WDHD1 degraders enhanced the sensitivity of platinum‐resistant ovarian cancer and non‐small‐cell lung cancer to platinum‐based drugs and radiotherapy in vitro and in vivo (Gou et al, 2022; Li et al, 2021). BZA degraded WDHD1 by inducing its ubiquitination.…”
Section: Introductionmentioning
confidence: 76%
“…Unfortunately, WDHD1 inhibitors are still in their infancy, and only one case of peptide has been reported (Wu et al, 2017). Screening among the existing compound library based on a high‐throughput screening platform for the WDHD1 luciferase reporter gene, we found several potential compounds that can inhibit the expression of WDHD1 at different degrees (Gou et al, 2022; Li et al, 2021). In the experiment, the estrogen receptor modulator bazedoxifene (BZA) showed a outstanding performance, it can significantly inhibit the expression of WDHD1 in a variety of cell lines at the administered dose.…”
Section: Introductionmentioning
confidence: 99%
“…This group has recently identified two potent And-1 inhibitors: bazedoxifene acetate and the novel compound [(E)-5-(3,4-dichlorostyryl)benzo[c] [1,2]oxaborol-1(3H)-ol], also known as CH3. 6 Both were used in the present study, each markedly enhanced therapeutic responses to ionizing radiation in CRC cells. While CH3 has yet to undergo clinical evaluation, bazedoxifene acetate is a third generation selective estrogen receptor modulator that first earned approval by the Food and Drug Administration (FDA) in 2013 in combination with conjugated estrogens as a treatment for post-menopausal osteoporosis.…”
Section: Commentarymentioning
confidence: 99%
“…Beyond providing new insights into And‐1 biology and DNA repair, the findings presented in this study have a direct path to translation. This group has recently identified two potent And‐1 inhibitors: bazedoxifene acetate and the novel compound [(E)‐5‐(3,4‐dichlorostyryl)benzo[c][1,2]oxaborol‐1(3H)‐ol], also known as CH3 6 . Both were used in the present study, each markedly enhanced therapeutic responses to ionizing radiation in CRC cells.…”
Section: Commentarymentioning
confidence: 99%
“…We recently identified two potent And‐1 inhibitors, CH3 and bazedoxifene (BZA). 9 Inhibition of And‐1 by these two inhibitors resensitized the resistant cells to IR (Figures 4I,J , S5G ).…”
mentioning
confidence: 95%